The role of 'mediating forms of representation' in learning design - Conole, Gráinne (Proceedings of the International Conference on Networked Learning, 2006)
There are a plethora of learning theories which can use to guide the development of learning activities. In addition there are now a rich variety of ICT tools which can potentially be used in innovative ways to support the implementation of these learning activities. Despite this the actual range of learning activities which demonstrate a variety of pedagogical approaches and innovative use of ICT tools is limited. Practitioners lack the necessary skills to make informed choices and are confused by the plethora of choices. This paper defines and describes the range of mediating artefacts (or mediating forms of representation) which are increasingly being used by practitioners to make more informed judgements in designing learning activities. It will consider how these mediating artefacts facilitate decision making.